COGNITIVE APPEALS IN IBN JARIR AL-TABARI’S EXEGESIS: A MODERN ANALYTICAL PERSPECTIVE ON JAMI’ AL-BAYAN (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This paper explores the cognitive appeals embedded in the Qur’anic exegesis of Ibn Jarir al-Tabari (d. 923 CE) through his magnum opus Jami’ al-Bayan fi Ta’wil Ay al-Qur’an. The analysis examines how al-Tabari interprets verses that call for reflection (tafakkur), focusing on the interplay between rhetorical style, linguistic precision, and theological depth. By comparing al-Tabari’s methods with classical scholars such as al-Zamakhshari and modern exegetes like Wahbah al-Zuhayli, this study sheds light on how cognitive and reflective dimensions are central to classical tafsir. Relevant Qur’anic verses are cited and analyzed in both Arabic and English to underscore their intellectual and spiritual resonance.